ANALISIS KONFLIK SUMBERDAYA HUTAN DI KAWASAN KONSERVASI - Marina, Ina; Hadi Dharmawan, Arya (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
This study focused on the history of natural resource conflict, the actors who involved in conflicts in Gunung Halimun-Salak National Park and the forms of conflict resolutions that has been done. The approach in this study is a qualitative approach with a case study methode. The data obtained with depth interview techniques, observation, and documentation. This study was conducted in Kampung Sinar Resmi, that belongs to the Kasepuhan Sinar Resmi community. This location is a place where community’s cultivating land overlap with the claim of Gunung Halimun-Salak National Park, thus causing a lack of clear boundaries and result in forest resource conflicts. Forest resource conflicts are caused by four different conflicts sources, namely differences in perceptions, different values, different interests, and differences in recognition of ownership rights. The forms of conflict resolution that has been done is negotiation, but doesn’t reach the agreement.